1989
DOI: 10.1016/0735-1097(89)90317-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of reperfusion injury with intracoronary calcium channel antagonists and reduced coronary free calcium concentration in regionally ischemic, reperfused porcine hearts

Abstract: The effect of intracoronary diltiazem, EGTA (ethylene-bis-(beta-aminomethylether)-N,N'-tetraacetic acid), nifedipine, verapamil and isotonic saline solution as placebo on reperfusion injury was investigated in regionally ischemic, reperfused porcine hearts. The left anterior descending coronary artery was distally occluded for 45 min and was reperfused for 3 days. Intracoronary infusion was started immediately before reperfusion and continued during 45 min of reperfusion. Infarct size was determined as the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…Anesthesia, medication, and general surgical procedures have been described in detail in previous studies [3,10]. Twelve male and female farm pigs (Department of Agriculture, University of GSttingen, FRG), weighing 38-47 kg, were used.…”
Section: Me~o~mentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia, medication, and general surgical procedures have been described in detail in previous studies [3,10]. Twelve male and female farm pigs (Department of Agriculture, University of GSttingen, FRG), weighing 38-47 kg, were used.…”
Section: Me~o~mentioning
confidence: 99%
“…Indirect evidence for the existence of postischemic cell death has come from studies that demonstrated that the administration of different agents at the time of reperfusion aimed to scavenge oxygen free radicals [1], improve perfusion [2], lower coronary free calcium [3], or inhibit the contractile apparatus [4] were able to reduce infarct size in different species by 28-75%. However, many of the positive studies have been questioned by negative findings [reviewed in [5][6][7].…”
mentioning
confidence: 99%
“…28 When tested in larger animal preparations, calcium antagonists decreased infarct size. 29 Despite this evidence, the results of the corresponding clinical trials have been unequivocally negative, irrespective of whether the calcium antagonists were administered before, during or after ischemia. 30, 31 Another possibility of reducing calcium overload is to inhibit the sodium-hydrogen exchange.…”
Section: Calcium Paradoxmentioning
confidence: 99%
“…At the time of myocardial reperfusion, there is an abrupt increase in intracellular Ca 2+, secondary to sarcolemmal membrane damage and oxidative stress-induced dysfunction of the sarcoplasmic reticulum. These two forms of injury overwhelm the normal mechanisms that regulate Ca 2+ in the cardiomyocyte, a phenomenon termed the calcium paradox [127]. The result is intracellular and mitochondrial Ca 2+ overload, inducing cardiomyocyte death by causing hypercontracture of the heart cells.…”
Section: General Aspectsmentioning
confidence: 99%